2019
DOI: 10.1051/matecconf/201929901011
|View full text |Cite
|
Sign up to set email alerts
|

Sweat glands module with integrated sensors designed for Additive Manufacturing

Abstract: Lead by the results of our previous work, in which we designed the sweat glands prototype according to AM (Advanced Manufacturing) requirements, in this study we aimed to integrate the previously manufactured channels into a stereolithography (SLA)-manufactured module, in order to avoid support structures inside the channels and the model cavities. That was achieved by distributing the channels in the manner which approximates the sweat glands distribution on an equivalent real body part and to be able to adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Thus, an anatomical module was designed that offer the possibility to bring the same amount of liquid to the required surface. The armpit area was selected to develop a complex sweat glands module [1]. Regarding the AM possibilities, various scientific papers shown that 3D printing technologies can produce complex prototypes for different applications under the "layer by layer" principle [2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, an anatomical module was designed that offer the possibility to bring the same amount of liquid to the required surface. The armpit area was selected to develop a complex sweat glands module [1]. Regarding the AM possibilities, various scientific papers shown that 3D printing technologies can produce complex prototypes for different applications under the "layer by layer" principle [2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%